Plasma ACE2 activity is persistently elevated following SARS-CoV-2 infection: implications for COVID-19 pathogenesis and consequences. Issue 5 (13th May 2021) - Patel, Sheila K.; Juno, Jennifer A.; Lee, Wen Shi; Wragg, Kathleen M.; Hogarth, P. Mark; Kent, Stephen J.; Burrell, Louise M.
Coronavirus disease 2019 (COVID-19) causes persistent endothelial inflammation, lung, cardiovascular, kidney and neurological complications, and thromboembolic phenomena of unclear pathogenesis [1]. Severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) utilises the catalytic site of full-length membrane-bound angiotensin converting enzyme 2 (ACE2) for host cell entry [2], which is thought to downregulate membrane-bound ACE2, and thus contribute to ongoing inflammation due to loss of a degradative pathway for angiotensin II. In healthy individuals, ACE2 exists primarily in its membrane-bound form with very low levels of the catalytically active ectodomain of ACE2 present in the circulation [3]. However, in patients with cardiovascular disease, there is increased "shedding" of ACE2, and higher circulating levels are associated with downregulation of membrane-bound ACE2 [4]. Plasma ACE2 activity is persistently elevated in patients after COVID-19 infection. Larger studies are needed to determine if this identifies people at risk of prolonged illness following COVID-19. https://bit.ly/2XQlrYF